2005
DOI: 10.1111/j.0022-202x.2004.23586.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Restricted Vβ Usage in the Leukemic Phase of Cutaneous T Cell Lymphoma

Abstract: Antibodies directed against the beta chain of the T cell receptor (anti-Vbeta antibodies) are useful to identify the Vbeta repertoire of T cells in various diseases and to quantify numbers of Vbeta-bearing T cells. The goals of this study were to identify Vbeta+ cases of leukemic phase cutaneous T cell lymphoma (CTCL) and to compare the percentage of positive calls with other measures of blood tumor burden, i.e., lymphocyte subsets with a CD4+CD7- and CD4+CD26- phenotype and Sezary cell counts. Thirty-three of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 106 publications
(135 reference statements)
3
33
1
Order By: Relevance
“…Moreover, several TCR Vβ families were constantly under-represented in SS (TCR-Vβ 3, 4, 9, 14, 16, 18 and 21.3), thus defining another distinctive marker of this extranodal T-cell lymphoma. Similar results were observed by Vonderheid et al 38 although there were no TCR-Vβ2 positive cases in their cohort. There are at least 65Vβ segments in the human TCR beta V (TRVB) locus located on chromosome 7 at band 7q34.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, several TCR Vβ families were constantly under-represented in SS (TCR-Vβ 3, 4, 9, 14, 16, 18 and 21.3), thus defining another distinctive marker of this extranodal T-cell lymphoma. Similar results were observed by Vonderheid et al 38 although there were no TCR-Vβ2 positive cases in their cohort. There are at least 65Vβ segments in the human TCR beta V (TRVB) locus located on chromosome 7 at band 7q34.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is important because, for decades, SEs have been suspected to play a tumor-promoting role in CTCL. 39,40,45,50,[68][69][70] We now propose that SEA-mediated cross talk between malignant and nonmalignant T cells triggers oncogenic STAT3 activation in vivo. Our findings provide a plausible explanation for clinical observations indicating that SE-producing staphylococci promote tumor growth and aggravate the disease and, conversely, that antibiotic therapy may halt disease progression and even induce tumor regression in some CTCL patients.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, analysis in biopsies is more adapted to unambiguous identification of the malignant T-cell clone since, as mentioned previously, clonal circulating T cells are frequently observed in non-malignant conditions, leading to potential confusion between reactive and tumor cells. 17 On the basis of the promising results obtained from blood samples, [11][12][13][14][15][16] we used flow cytometry to assess the expression of 25 Vb chain members of the TCR. Indeed, T-cell clones use a single Vb domain and can thus be identified by the abnormal expansion of one Vb family or by a restricted TCR-Vb repertoire (see Materials and methods).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preferential use of some Vb families has been reported in leukemic phase of cutaneous T-cell lymphoma 16 and T-CD4 þ large granular lymphocytic proliferations in which the clone specificity for hCMV peptides has been demonstrated. 11,39 By contrast, Lima et al 11 reported that CD8 þ T-cell large granular lymphocytic proliferations in blood samples showed a pattern of Vb distribution that mimics the frequency at which individual Vb families are represented in normal CD8 þ T cells, suggesting that CD8 þ T-cell large granular lymphocytic leukemia cells were clonally transformed in a random manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation